Analysis on the frequency of passenger train delay (Keretapi Tanah Melayu Berhad) / Khadijah Ishak - Ishak, Khadijah (1994)
This research is on the analysis of the passengers train delay. The main objectives are to analyse delays that always happen during the running of train. These concludes with the main reasons leading to delay, types of train that contribute most to delay, cost incurred, time of the year that delays always occur and examine the aggregate level of delay. The study has been done including analysing the opinions, views and research regarding the matter. The information has been.gathered from personal interviews and personal observation. Apart from that, I have also referred from the published statistical data, pamphlets, brochures, text books, journals and newspaper cuttings. Generally, the overall KTMB's passengers train operation has now improved.